Placental macrophages present distinct polarization pattern and effector functions depending on clinical onset of preeclampsia - Mercnik, Monika Horvat; Schliefsteiner, Carolin; Fluhr, Herbert; Wadsack, Christian (Frontiers in Immunology, 2023)
Hofbauer cells (HBCs) are resident macrophages of the human placenta, regulating immune tolerance and tissue homeostasis. HBCs of a normal placenta (CTR) exhibit mainly an anti-inflammatory M2 phenotype. Under exaggerated chronic inflammation during pregnancy, as in preeclampsia (PE), a phenotypic switch towards M1 polarization has been proposed. PE, defined as maternally derived syndrome can be distinguished into two different entities: early-onset (EO) preeclampsia and late-onset (LO) preeclampsia. Although the clinical presenting characteristics overlap, both can be identified by biochemical markers, heritability, and different maternal and fetal outcomes. To date, no study has specifically investigated polarization and phenotype of EO- and LO-PE HBCs and looked at possible changes in HBC functionality. Primary HBCs were isolated from CTR and PE placentae. First, in vitro morphological differences were observed between CTR and PE HBCs, with both PE groups exhibiting features of M1 macrophages alongside M2 forms. Interestingly, a different polarization pattern was observed between EO- and LO-PE HBCs. EO-PE HBCs develop a tissue remodeling M2 phenotype that is strongly shifted toward M1 polarization and showed a significant upregulation of CD86, TLR4, and HLA-DR. Furthermore, this pro-inflammatory signature is corroborated by higher expression of IRF5 and of NOS2 (p≤0.05). However, their M2 characteristics is reflected by significant TGF-β secretion and ARG1 expression. In contrast, LO-PE HBCs developed a phagocytic CD209-low M2 phenotype in which the M1 pattern was not as pronounced as they downregulated the NOS2 gene, but expressed increased levels of pro-inflammatory CD80 and TLR1 (p≤0.05). The enhanced phagocytosis and MMP-9 secretion alongside the increased secretion of anti-inflammatory IL -4, IL -13 and TGF-β in both EO- and LO-PE HBCs suggests their adaptive role and plasticity in resolving inflammation and tissue homeostasis.